PENGARUH KESEHATAN KERJA,KESELAMATAN KERJA,DAN LINGKUNGAN KERJA FISIK TERHADAP PRODUKTIVITAS KINERJA KARYAWAN - Auliya azahra hafizh; Usiono Usiono (JOURNAL SAINS STUDENT RESEARCH, 2024)
The influence of health, safety, workload and work environment is very important because employees need protection from accidents, illnesses and uncomfortable conditions while working in order to achieve optimal productivity. The purpose of this research is to determine whether there is an influence of work safety, work health and work environment on the work productivity of employees of PT. Sari Dumai Oleo (Apical Group). This research consists of four variables, namely Occupational Safety and Health (K3) (X1), Work Environment Physical (X2), and Employee Work (Y). This research uses data collection methods in the form of interviews, observations, questionnaires. The data analysis methods used are descriptive analysis, data quality testing, classical assumption testing. The results of the analysis state that: (1) Occupational Safety and Health (K3) has a positive and significant influence on Employee Performance, (2) Workload has a positive and significant influence on Employee Performance,(3) Physical Work Environment has a positive and significant influence on Employee Performance.